Rekayasa Media Pembelajaran dalam PAI: Menyatukan Visual, Naratif, dalam Nilai Keislaman - Rini Kurniati; Widya Amanda; Gusmaneli (Educational Journal, 2026)
The design of Islamic Religious Education (PAI) learning media plays a crucial role in creating an effective and valuable learning process. Media is understood as a means of communication that conveys learning messages through various forms, particularly visual and narrative. In PAI, visual media such as posters, infographics, concept maps, and videos help clarify abstract concepts with a concrete and engaging presentation. Meanwhile, narrative media such as stories, comics, drama, and animation strengthen the understanding of Islamic values ​​through storylines that engage students' cognitive and affective aspects. The integration of visuals and narratives enables more holistic learning, as it combines representation with information, leveraging the power of storytelling to facilitate the internalization of values. This approach aligns with the goals of Islamic education, which emphasize the integration of knowledge, values, and morals. With appropriate media design and grounded in Islamic principles, PAI learning can be more engaging, meaningful, and capable of shaping students' religious character.